THE ROLE AND SIGNIFICANCE OF THE REVISED CONSTITUTION IN ENSURING HUMAN RIGHTS - Abdurahmon Yakubov (Scholar Express Journals, 2025)
This article provides a scientific analysis of how human and civil rights and freedoms are reinforced in the new edition of the Constitution of the Republic of Uzbekistan on the basis of innovative approaches, as well as their significance in legislation and legal practice
Keywords: Constitution; human rights; civil liberties